Acute Laryngeal Dyspnea as the First Presentation of Mantle Cell Lymphoma: A Case Report and Review of the Literature - Mounir Ababou; Hicham El Maaroufi; Adnane Hammani; Selim Jennane; El Mehdi Mahtat; Mohammed Mikdame; Kamal Doghmi (Case Reports in Hematology)
Introduction. Acute laryngeal dyspnea is a life-threatening emergency, and the causes in adults are most often laryngeal tumors or inflammatory edema. Lymphoma of the larynx and especially the mantle cell type is extremely rare. Case Presentation. We report a case of a 43-year-old woman with no particular pathological history. She presented with progressive dyspnea which has evolved towards an inspiratory bradypnea that worsened until she ultimately required an emergency tracheotomy. Biopsies revealed mantle cell lymphoma. The patient has been staged IVB MIPI 6, and she was treated by immunochemotherapy followed by ASCT. The therapeutic evaluation shows a complete remission, 18 months after, and the patient was always disease free. Conclusion. The laryngeal localization of the mantle cell lymphoma is extremely rare; it may present catastrophically with acute airway obstruction. The diagnosis is mostly histological, hence the interest of deep biopsy. Given its rarity, the therapeutic strategy must be discussed case by case in a multidisciplinary consultation meeting.